The Influence of Information Technology Adoption on the Financial Performance of Medan City MSMEs - Nasution, Ummi Kalsum; Irama, Ova Novi (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This research was carried out based on phenomena that exist in the city of Medan. shows that there is an increase in the quality of community businesses by using information technology. The number of MSMEs in the city of Medan is a very large number, but not all MSME actors understand how to use technology to support their businesses. Information technology has an influence on increasing sales and income of MSMEs, such as increasing market access, operational efficiency and personalization of services. This research looks at how influential information technology is on the financial performance of MSMEs in the city of Medan. This research obtained data from 3 sub-districts which were used as research samples. if the significance value is <0.05, it means that variable X has an influence on variable Y and if the significance value is >0.05, it means that variable As a result of squaring R from the output, the coefficient of determination (R2) is 0.897, so from this table it can be seen that Information Technology has a good influence on the financial performance of Medan City MSMEs. Keywords: Technology Adoption, MSMEs.